Innovation, creativity and governance 8 years on: Social dynamics of economic performance in city-regions. Issue 4 (1st October 2016) - Wolfe, David; Bramwell, Allison
Abstract : Confronting the challenges facing twenty-first century urban economies demands coherent responses that neither the private sector nor government operating alone can provide. Our research leads us to conclude that the capacity of city-regions for economic transformation depends not just on supportive public policies and favourable markets, but also on their underlying social and political structures. Many city-regions are experimenting with innovative institutional arrangements that seek to shape their future growth trajectories while attempting to mitigate the negative social consequences of innovation-intensive growth. Success in the contemporary knowledge-based economy depends not only on the innovative capabilities of local firms, the underlying strength of research infrastructure that supports those firms, and access to local pools of talent and creativity, but most fundamentally on the institutional structures that integrate the complex and diverse set of interests found in those city-regions into new more collaborative forms of civic governance.